Hubungan Status Pekerjaan, Pendapatan dan Kepatuhan Tablet Tambah Darah dengan Riwayat Ibu Hamil Anemia - Isma Salsabila; Eka Andriani; Milliyantri Elvandari3 (Universitas Pahlawan Tuanku Tambusai, 2025)
Anemia is a global problem experienced by all countries, especially developing countries. According to Basic Health Research data in 2018, the incidence of anemia among pregnant women in 2018 was 48.9%, while in 2013 it was 37.1%, resulting in an increase of 11.8%. Researchers are interested in conducting research related to